Filling in the knowledge gap: Observing MacroPlastic litter in South Africa's rivers. (January 2021) - Moss, Kerry; Allen, Deonie; González-Fernández, Daniel; Allen, Steve
Abstract: Only 12% of the world's published plastic research includes references to Africa despite it being a significant contributor to the global plastic waste and mismanagement problem (~88.5% of Africa's plastic waste is mismanaged). Ocean plastics are transported from land by rivers to the sea. However, source contextualization is complex. Many African rivers predominantly run alongside human settlements that host informal waste dumpsites. In this study a simple cost effective, easily deployed, consistent and replicable survey methodology was employed. The study quantified macroplastic in three rivers discharging into Algoa Bay, South Africa. The results indicated that industrial Swartkops and metropolitan Baakens Rivers both illustrate moderate plastic pollution (>3000 plastic particles/day), with the relatively natural Sundays River to showing minimal evidence of river macro plastic (<100 plastic particles/day). The types of plastic were noted using the RIMMEL app (premier African implementation), enabling proportional comparison of different plastic litter types to be completed. Highlights: Many rivers in significant plastic pollution contributing countries are unsurveyed RIMMEL provides a simple, consistent method to quantify river macroplastic Provision of the first plastic counts for 3 Port Elizabeth rivers, South Africa